The swab - Steer, Howard; St. Patrick's Race Club (Broken Hill, N.S.W.) (Broken Hill, N.S.W. : St Patricks Race Club, 1991)
Poster promoting the 26th annual race meeting of the St Patricks Race Club, Broken Hill. The upper half features Howard Steer's painting, The swab, which is offered to the highest bidder. The painting shows samples for drug testing being taken from a horse as it stands in front of a crowded grandstand. The lower half lists the races.
Caption title.
Painted image measures 36 x 39 cm.
Howard William Steer (1947-), born in and still resident of Broken Hill, is a still-active artist, illustrator and author, whose artistic style is classified as naive realism, and which he calls "story art".
St Patrick's Race Club, Broken Hill, was formed to help alleviate the desperate financial position of the local Catholic schools, and the inaugural race meeting was held on Saturday 19 March 1966. The event has grown to become the richest 'one day country race meeting' in Australia. (from the St Patrick's Race Club website http://stpatricks.org.au ).
Keywords: St. Patrick's Race Club ( Broken Hill, N.S.W.) -- Posters; Horse racing -- New South Wales -- Broken Hill -- Posters; Doping in horse racing -- New South Wales -- Broken Hill -- Posters; Posters, Australian; Australia -- Posters; Australian